Service user and community clinician design of a partially virtual diabetic service improves access to care and education and reduces amputation incidence. Issue 1 (11th January 2021) - Watt, Alastair; Beacham, Andrea; Palmer-Mann, Lynne; Williams, Amy; White, Jacqueline; Brown, Rebecca; Williams, Ellena; Richards, Gayle; White, Lyndon; Budge, Pauline; Darvall, Katy; Bond, Ed; et al.
Abstract : Introduction: Design of an integrated diabetes service based on needs of service users (persons living with diabetes) and community clinicians in a semirural low-income health district of the UK. Research design and methods: One hundred and eighty-five service users engaged through public meetings, questionnaires and focus groups. General practice staff contributed views through workshops and questionnaires. Analysis of feedback indicated service user needs for better access to education, dietary advice and foot care. General practice staff endorsed these views and requested regular access to secondary care in the community. Seven hundred persons registered with diabetes attended eight well-being events in the community. From 2017 virtual practice multidisciplinary patient reviews, virtual referral of foot cases and non-face-to-face helplines were developed. A National Health Service (NHS) approved 'App' and web-based personalized education support for those recently diagnosed with diabetes was introduced. Results: Engagement in education for those recently diagnosed with diabetes increased from 5% to 71%. Weight and hemoglobin A1c (HbA1c) levels before and 6 months after starting the program were 99.4±25 and 95.5±24.2 kg and 59.3±16 and 54.8±12.9 mmol/mol, respectively, p=0.00003 and 0.003. Of those engaging at well-being events, 44 had missed regular follow-up. One hundred and seventy-five cases were reviewed virtually with practice staff by the secondary care team avoiding referral to the hospital diabetic clinic. One hundred and seventy-six referrals were made to the virtual multidisciplinary diabetic foot team clinic. Major amputation incidence declined from 13 to 3 major procedures/10 000 per annum and minor amputation from 26 to 18/10 000. Percentage bed day occupancy by persons with diabetes fell significantly in the district general hospital. Conclusions: Integrated community-based diabetes care delivery has been achieved with partially virtual reviews. Patient education, secondary care in the community, access to dietetic advice and foot care outcomes have all improved.